GREENPEACE’S TRANSNATIONAL ADVOCACY STRATEGIES AGAINST NICKEL MINING IN RAJA AMPAT - Santioso, Claudia Marcia Anastasia; Sinaga, Melpayanty (BHUVANA: Journal of Global Studies, 2025)
This research aims to analyze the environmental diplomacy strategies employed by Greenpeace in opposing the mining project in Raja Ampat, Southwest Papua. This area is one of the global marine conservation sites threatened by the exploitation of natural resources carried out by mining companies. This study uses a descriptive qualitative approach with a case study method, sourcing data from official Greenpeace documents, such as reports, press releases, and campaign publications, relevant national and international journal articles and news, as well as interviews with Greenpeace Indonesia’s Forest Campaigner. The results show that Greenpeace employs four main strategies to maintain environmental diplomacy, such as: (a) media campaigns and global advocacy, (b) alliances with indigenous communities and local NGOs, (c) pressure through international channels, and (d) mobilization of public opinion based on ecological symbols and narratives. These strategies successfully built public pressure on the Indonesian government, resulting in a reevaluation of mining permits and, eventually, the temporary halting of all mining production activities in Raja Ampat.